Integrating sustainable development into national frameworks : policy approaches for key sectors in small states - Strachan, Janet (Commonwealth Secretariat GB, 2011)
Addresses issues of sustainable development for small states and islands, to bring policies and programmes for sustainable development from the shadows into the mainstream of decision-making at all levels of governance and in all sectors. Covers eight of the twenty issues that have outlined in the Mauritius Strategy as being important for the sustainable development of SIDS - disaster management, marine resources, freshwater resources, land resources, energy resources, tourism resources and trade.